Pengaruh Penggunaan Smartphone Terhadap Keterampilan Menyimak Siswa Kelas IV SD Kartika XIII-1 Ambon: Indonesia - Letahiit, Febriyanti; Sahetapy, Sarah; Ririhena, Ribka L. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of smartphone use on the listening skills of fourth-grade students at Kartika XIII-1 Ambon Elementary School. The method used is quantitative research with a correlational approach. The results show that smartphone use does not have a significant effect on the listening skills of fourth-grade students at Kartika XIII-1 Ambon Elementary School. The post-test scores did not show an increase compared to the pre-test, with a low N-Gain category. This indicates that smartphones are used more for entertainment than for learning. The questionnaire and observation results support the finding that smartphone use has a more negative impact on students' concentration and listening skills.